The Global Financial Crisis : An Anatomy of Global Growth - Matheson, Troy (IMF Working Papers; Working Paper ;, 2013)
The global financial crisis was a stark reminder of the importance of cross-country linkages in the global economy. We document growth synchronization across a diverse group of 185 countries covering 7 regions, and pay particular attention to the period around the global financial crisis. A dynamic factor model is used to decompose each country's growth into contributions from global, regional, and idiosyncratic shocks. We find a high degree of global synchronization over 1990 to 2011, particularly across advanced economies. Examining the period around the global financial crisis, we find global shocks had large and widespread effects on growth, with more diversity in growth experiences in the early part of the recovery. In a recursive experiment, we find rising global growth synchronization just prior to the crisis, largely resulting from a shift in the importance of global shocks between countries. In contrast, the crisis period caused a much more widespread increase in growth synchronization, and was followed by a similarly pervasive decrease in synchronization in the early recovery.